General-to-specific modelling - Campos, Julia; Ericsson, Neil R.; Hendry, David F. (Cheltenham : Edward Elgar, 2005)
This important two-volume collection focuses on a central method used in selecting models, like simplification of an initially general model that adequately characterizes the empirical evidence within the investigators' theoretical framework. The volumes feature a wealth of evidence that has accrued over the last five years displaying its excellent abilities for model selection, based on Monte Carlo studies of automatic algorithms.
Includes bibliographical references and index.
oif 15/04/15
Loans
Keywords: Econometric models